Find the value of n.


22n=418

Answers

Answer 1
Answer:

19

418 divided by 22 is equal to 19

Answer 2
Answer:

And that’s the answer


Related Questions

My daughter needs help with homework.
Sally has 2 cups of flour .she uses 3/4 cup to bake muffins and 3/8 cup flour to bake cookies and 3/8 cup flour for pancakes .how much flour does Sally have left?
Consider the table of the powers of 8.Answer these questions about the powers of 8.What is the pattern as the exponents decrease?What is the value of each variable in the table?a = b = c =
What is 12.9 divided by 0.6
Complete the equation of the graphed linear function in point-slope form.y – 6= ??? (x – ?? )Please explain!!

How many ounces of trail mix are in a bag that weighs 0.681 kilograms? Input only numeric values. (1 pound = 0.454 kg and 1 pound = 16 ounces)

Answers

.681kg/1bag x 1lb/.454kg x 16oz/1lb = 24oz/1bag

The point (0,0) is a solution to which of these inequalities?

Answers

The point (0,0) is a solution of (y - 5 < 3x - 4) and this can be determined by substituting the value of (x = 0) and (y = 0).

Given :

Point  --  (0,0)

Check all the options in order to determine the inequalities whose solution is (0,0).

A) y + 5 < 3x - 4

Substitute the value of (x = 0) and (y = 0) in the above in equality.

5 < -4 which is not true. Therefore, this option is incorrect.

B) y - 4 < 3x - 5

Substitute the value of (x = 0) and (y = 0) in the above in equality.

-4 < -5 which is not true. Therefore, this option is incorrect.

C) y + 5 < 3x + 4

Substitute the value of (x = 0) and (y = 0) in the above in equality.

5 < 4 which is not true. Therefore, this option is incorrect.

D) y - 5 < 3x - 4

Substitute the value of (x = 0) and (y = 0) in the above in equality.

-5 < -4 which is true. Therefore, this option is correct.

For more information, refer to the link given below:

brainly.com/question/19491153

D because -4 is greater than -5

Melissa and Joey enjoyed dinner at a restaurant. They paid the waiter $100.50 plus a 20% tip. How much did each person pay if they split the total bill in half?

Answers

In the question it is already given that Melissa and Joey would have to share the total bill along with the tips at the resturant during their dinner. The paid the water an amount of $100.50 and additional 20% tip.Firstly we have to find the amount of the tip and then add with the total amount to calculate the total amount paid by both of them.
Amount of tips paid to the waiter = (20/100) * 100.50 dollars
                                                     = 2010/100 dollars
                                                     = 20.10 dollars
So Melissa and Joey paid $20.10 as tips to the waiter.
Then the total amount paid  by both of them = (100.50 + 20.10) dollars
                                                                       = 120.60 dollars
Then the amount paid by Melissa and Joey = 120.60/2 dollars
                                                                     = 60.3 dollars.
So Melissa and Joey will individually pay $60.3 each.

They both paid 60.30 welcome


What is 4 1/5 + 8 2/7 equal.

Answers

The answer is 123/12

With which values ​​of the argument the function acquires a value equal to144 y =  \frac{1}{9x {}^(2) }

Answers

Answer:

x=(1)/(36) \, \,and\,\, x=-(1)/(36)

Step-by-step explanation:

To find at which values of the argument the function renders 144, we need to solve for "x" in the equation when y is 144:

y=(1)/(9\,x^2)\n144=(1)/(9\,x^2)\n144\,x^2=(1)/(9) \nx^2=(1)/(9\,(144)) \nx^2=(1)/(1296) \nx=+/-\sqrt{(1)/(1296) } \nx=+/-(1)/(36)

Therefore there are two solutions: one is 1/36 and the other one is its opposite; -1/36

Answer:

Step-by-step explanation:

hello :

solve : 1/9x² = 144

x² = 144×9

x² =(12×3)²    means : x² =36²

so : x=36 or x= -36

suppose the solution x = 6 increases to x = 9, and the left side of the equation stays the same. How would the right side need to chang if the solution is now x = 9

Answers

Answer:

The original solution of the equation

  x=6

Adding 3 on both sides, gives

x+3=6+3

x+3=9

 x=9-3

So,Addition of 3 on left hand side or subtraction of 3 from 9 in right hand side gives solution x=9.

X = 9 - 3, does this help?